Effects of concurrent training with self-selected intensity on the physical fitness of hypertensive individuals. - Silas Nery de Oliveira; Antônio Renato Pereira Moro; Wagner Jorge Ribeiro Domingues; Ewerrton de Souza Bezerra (Universidade Estadual de Maringá, 2018)
The objective of this study was to verify the influence of i) a concurrent exercise program with self-selected intensities, and ii) order of exercise execution, on the cardiovascular indicators and functionality of medicated hypertensive patients. Seventeen individuals were allocated to one of two concurrent training groups:  aerobic-resistance (7 men) and resistance-aerobic (3 men; 7 women). Each group underwent cardiovascular (heart rate, systolic and diastolic arterial pressure) and functional (6MWT, TUG, flexibility and hand grip strength) evaluations pre and post training. The training occurred over 9 weeks.  Resistance exercises were performed with an elastic tube and participants' body weight; self-selected intensity was supported by the OMNI-RES scale. The aerobic exercise was performed using a cycle ergometer with intensity measured by the Borg scale. A two-way ANOVA for repeated measures was used for comparisons between training programs, followed post  hoc by the Bonferroni test, adopting p<0.05. There were no significant changes in the cardiovascular and functional capacity indicators from pre- to post-intervention, and there were no significant interactions based on the order of the training program. The results suggest that a concurrent training program with self-selected intensity, regardless of order of training, may promote similar changes in cardiovascular and functional health indicators in individuals with controlled hypertension.